2018
DOI: 10.1002/bit.26707
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of depth filter components to protein adsorption in bioprocessing

Abstract: Depth filtration is widely used in downstream bioprocessing to remove particulate contaminants via depth straining and is therefore applied to harvest clarification and other processing steps. However, depth filtration also removes proteins via adsorption, which can contribute variously to impurity clearance and to reduction in product yield. The adsorption may occur on the different components of the depth filter, that is, filter aid, binder, and cellulose filter. We measured adsorption of several model prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
1
29
2
Order By: Relevance
“…Ultipor™ VF Grade DV50 (Pall Corp.) mentioned as preferred filters with preferred clearance of 5 LRV and at least 85% recovery of AAV (Hermens & Smith, 2013). In another patent, Genzyme references the use of various viral retentive filters for the removal of viruses from an AAV1 feed stream, such as Asahi KASEI and Pall virus filters, and the use of Millipore's Viresolve® NFR filter (Paulene, Gagnon, Nichols, & Thorne, 2010).…”
Section: Aav8mentioning
confidence: 99%
“…Ultipor™ VF Grade DV50 (Pall Corp.) mentioned as preferred filters with preferred clearance of 5 LRV and at least 85% recovery of AAV (Hermens & Smith, 2013). In another patent, Genzyme references the use of various viral retentive filters for the removal of viruses from an AAV1 feed stream, such as Asahi KASEI and Pall virus filters, and the use of Millipore's Viresolve® NFR filter (Paulene, Gagnon, Nichols, & Thorne, 2010).…”
Section: Aav8mentioning
confidence: 99%
“…Cell/debris removal occurs on both the external surface and throughout the depth of the filter due to sieving/straining by the porous matrix, while impurity removal occurs by a combination of electrostatic, hydrophobic, hydrogen bonding, or potentially mixed‐mode interactions. Khanal et al 14 showed that adsorption of small impurities (like lysozyme or β‐lactoglobulin) in depth filters containing either diatomaceous earth (Celite) or perlite is primarily driven by electrostatic interactions arising in large part from the positively charged polymeric binder, leading to greater removal of negatively charged proteins. In contrast, the removal of DNA was found to be a strong function of the DNA size 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Typical commercial depth filters contain cellulose or polypropylene fibers, which provide the matrix structure of the filter; a high surface area filter aid like diatomaceous earth (DE), perlite, or activated carbon; and a binder, which insures the overall physical stability of the complex structure. 13 Cell/debris removal occurs on both the external surface and throughout the depth of the filter due to sieving/straining by the porous matrix, while impurity removal occurs by a combination of electrostatic, hydrophobic, hydrogen bonding, or potentially mixedmode interactions. Khanal et al 14 showed that adsorption of small impurities (like lysozyme or β-lactoglobulin) in depth filters containing either diatomaceous earth (Celite) or perlite is primarily driven by electrostatic interactions arising in large part from the positively charged polymeric binder, leading to greater removal of negatively charged proteins.…”
mentioning
confidence: 99%
“…Depth filters are a class of filters of a sponge-like texture, wherein particles are retained throughout the entire filter bed that is typically composed of polymer, binder and a filtration aid such as diatomaceous earth. For some depth filters, the media bears a charge for electrostatic retention of host cell proteins and DNA [184,185], with diatomaceous earth showing improved feed capacity although at high concentration it can lower LV titre [186]. In some small-scale studies, the use of multiple depth filter media, including cellulose-based and synthetic media (such as polyacrylic fibre with silica filter aids), has shown 90% turbidity reductions whilst maintaining high recovery of non-enveloped vectors, such as simian adenovirus based vectors [187].…”
Section: Vector Filtration: Initial Clarificationmentioning
confidence: 99%